2003
DOI: 10.5194/npg-10-453-2003
|View full text |Cite
|
Sign up to set email alerts
|

Response of a global atmospheric circulation model to spatio-temporal stochastic forcing: ensemble statistics

Abstract: Abstract. The response of a simplified global atmospheric circulation model (PUMA) to spatiotemporal stochastic forcing is analyzed using the statistical measures originally developed for ensemble forecast evaluation. The nontrivial effects of time and length correlations of the stochastic forcing on the ensemble scores (e.g. spread and 'error') are studied. A maximum for these scores is observed to occur for specific values of the correlation time. The effects of multiplicative and additive contributions of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…The results of this review corroborate the importance of considering a certain level of noise for improving the performance of climate models to explain nonlinear behavior, including noise-induced transitions between different regimes. [36][37][38][39][40][41][42][43][44] Most AOGCM models currently used have not taken into account processes below certain temporal and spatial scales. 56,57 This review addresses the role of stochastic sources in climate models and claims the importance of the study of these sources to understand the fate of the climate system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this review corroborate the importance of considering a certain level of noise for improving the performance of climate models to explain nonlinear behavior, including noise-induced transitions between different regimes. [36][37][38][39][40][41][42][43][44] Most AOGCM models currently used have not taken into account processes below certain temporal and spatial scales. 56,57 This review addresses the role of stochastic sources in climate models and claims the importance of the study of these sources to understand the fate of the climate system.…”
Section: Discussionmentioning
confidence: 99%
“…35 Transition probabilities are known to depend sensitively on noise levels. [36][37][38] Considering that the full spectrum of spatial and temporal scales exhibited by the climate system will not be resolvable by models for decades, the stochastic techniques offer a direct, suitable, and computationally economical solution.…”
Section: Stochastic Forcingmentioning
confidence: 99%
“…In that case, the stochastic process appears as multiplicative noise which, as is well known, can substantially change the dynamical behavior of not only nonlinear systems (Horsthemke and Léfèver 1984;Landa and McClintock 2000;Sura 2002), but also linear systems. The potentially significant role of multiplicative noise to improve the representation of subgrid-scale phenomena in models of the climate systems has been stressed in several studies (e.g., Buizza et al 1999;Palmer 2001;Sardeshmukh et al 2001;Pérez-Muñuzuri et al 2003;Sura 2002). Sardeshmukh et al (2001) introduced multiplicative noise in the linearized barotropic vorticity equation, and found that the mean stationary wave response to steady forcing was amplified when the damping parameter fluctuated, but was weakened (in a scale-dependent manner) when the ambient flow fluctuated.…”
Section: Stochastically Perturbed Rossby Wavesmentioning
confidence: 99%
“…When noise is added, the random perturbations increase the likelihood of the particle to overcome the potential barrier and move to the other state. This phenomenon is known as the paradigm of stochastic resonance (figure 1) and plays an important role in the transition probabilities which are known to depend on sensitivity to noise levels (Gammaitoni et al, 1998;García-Ojalvo & Sancho, 1999;Pérez-Muñuzuri et al, 2003;Lorenzo et al, 2003). Fig.…”
Section: The Role Of Stochastic Forcingsmentioning
confidence: 99%